Heating Up: How Early Twitter Marketing Gave Rise to Organic Word-of-Mouth About Heated Tobacco Products. (December 2022) - Kostygina, Ganna; Tran, Hy; Kim, Yoonsang; Czaplicki, Lauren; Kierstead, Elexis; Kreslake, Jennifer; Emery, Sherry; Schillo, Barbara
Social media are an important marketing platform for emerging tobacco products. Heated tobacco products (HTPs) have been introduced in a limited number of local test markets in the United States as potentially reduced-exposure tobacco products. HTPs can be used to heat tobacco as well as marijuana. However, due to growing digital media promotion of these products, it is possible that public knowledge and purchasing opportunities extend beyond test markets. Research on HTP social media promotion is sparse. The objective of the present study is to assess the amount and characterize the content of HTP-related messages on Twitter. We used keyword rules to collect HTP-related posts from the Twitter Historical Powertrack from 1 August 2016 to 31 July 2021. Posts were coded for type (organic, commercial), promotional strategies (e.g., discounts, event promotion), and marijuana co-use mentions using a combination of machine learning methods and human coding. Keyword filters captured 121, 012 relevant tweets posted over the period of data collection, with 46, 013 (38.02%) tweets featuring commercial content. Findings revealed that there was a two-fold increase in the monthly volume of messages from August 2016 to July 2021. The proportion of organic tweets increased from 29% of all tweets in August 2016 to 73.5% in July 2021. Approximately 20.6% of tweets included mentions of marijuana, and 5, 243 posts (4.3%) contained links to online retailers. Promotional tweets featured event promotion, discounts, reduced harm appeals, and fashion appeals. Tobacco control and substance use prevention initiatives should include efforts to monitor the role of social media in promoting organic word-of-mouth and normalizing novel tobacco products.